Keeping your cool: Possible mechanisms for enhanced exercise performance in the heat with internal cooling methods - Siegel, R.; Laursen, P. B. (Sports Medicine, 2012)
Exercising in hot environments results in a rise in core body temperature; an effect associated with impaired performance over a variety of exercise modes and durations. Precooling has become a popular strategy to combat this impairment, as evidence has shown it to be an effective method for lowering pre-exercise core temperature, increasing heat storage capacity and improving exercise performance in the heat. To date, the majority of precooling manoeuvres have been achieved via external means, such as cold water immersion and the application of cooling garments. However, these methods have been criticized for their lack of practicality for use in major sporting competitions. Recent evidence has shown that internal or endogenous cooling methods, such as drinking cold fluids or ice slurries, are able to lower core temperature and enhance endurance performance in the heat. These methods may be more advantageous than current forms of precooling, as ingesting cold fluids or ice slurries can be easily implemented in the field and provide the additional benefit of hydrating athletes. While the precise mechanisms responsible for these performance enhancements are yet to be fully explained, the effect of ice ingestion on brain temperature, internal thermoreception and sensory responses may be involved. This article addresses the evidence supporting the use of endogenous cooling methods for improving endurance performance in the heat, as well as discussing the potential mechanisms behind the improvements observed and providing practical recommendations to optimize their success.